Magnetic resonance imaging-navigated argon-helium cryoablation therapy against a rabbit VX2 brain tumor - WANG, YANG (Exp Ther Med, 2015)
The aim of the present study was to investigate the feasibility of interventional magnetic resonance imaging (MRI)-guided and monitored argon-helium cryoablation for the treatment of brain tumors in rabbits. In addition, the present study evaluated the associations between imaging and pathology, the therapeutic effects and the effects on the surrounding normal tissues. A total of 14 rabbits were equally divided into groups C and D. Under general anesthesia, the skull was drilled and tumor blocks were implanted. Subsequently, a New Zealand rabbit VX2 brain tumor model was successfully established. Rabbits in group C were treated with argon-helium cryoablation and those in group D did not undergo any treatment (control). Regular postoperative MRI scanning was performed to observe the changes in tumor size, and the survival times of the rabbits in groups C and D were recorded. The extent of necrosis in the brain tumor exhibited a significant correlation with the freezing time of cryoablation, and the necrotic region was shown to be the same size as the ice ball. The survival times of the rabbits in the treatment group (group C) were significantly prolonged. Therefore, the observations of the present study demonstrated that the VX2 brain tumor model, produced using an improved tumor block implantation method, was stable and suitable for MRI observation and interventional study. In addition, argon-helium cryoablation was shown to be a safe and feasible therapeutic method for the treatment of brain tumors, and was demonstrated to significantly increase the survival times of the brain tumor-bearing rabbits.